2016
DOI: 10.1097/ico.0000000000000817
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Wound Dehiscence Post–Penetrating Keratoplasty

Abstract: Wound dehiscence is a lifelong risk after PK regardless of the age, indication for corneal transplant, and time since transplant. A better visual outcome was associated with retained pseudophakia and clear corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…According to Tran et al, the longest was 20 years [ 13 ]. All traumatic WDs were observed to occur in the corneal graft-host interface [ 3 , 14 ], and our finding is consistent with it. This phenomenon indicated that the tensile strength of corneal graft-host junction after keratoplasty was weaker than original corneal tensile strength.…”
Section: Discussionsupporting
confidence: 90%
“…According to Tran et al, the longest was 20 years [ 13 ]. All traumatic WDs were observed to occur in the corneal graft-host interface [ 3 , 14 ], and our finding is consistent with it. This phenomenon indicated that the tensile strength of corneal graft-host junction after keratoplasty was weaker than original corneal tensile strength.…”
Section: Discussionsupporting
confidence: 90%
“…The amount of leakage from different areas can thus be observed. 2 Other modalities are sometimes also employed to diagnose occult wound leaks, such as ultrasound biomicroscopy as was described by Sicco et al 3 The treatment modality will depend on the type and extent of leakage present. In the presence of a flat anterior chamber, the wound leak should be urgently closed in the operating room.…”
Section: Complications Related To Wound Closurementioning
confidence: 99%
“…In the presence of a flat anterior chamber, the wound leak should be urgently closed in the operating room. 2 The presence of iris prolapse, even in the absence of a flat chamber, which will increase the risk for infection, should also be immediately surgically repaired in the operating room. 4 The urgency is to avoid contamination that could lead to infection, as well as to avoid prolonged contact between the corneal endothelium and other structures, which may ultimately lead to endothelial cell death and graft failure.…”
Section: Complications Related To Wound Closurementioning
confidence: 99%
See 1 more Smart Citation
“…Dehiscence may occur secondary to traumatic or non-traumatic causes. Human-induced injuries in young patients, or falls in the elderly, account for the majority of traumatic cases,8,12,20 while non-traumatic causes include suture removal, microbial keratitis or spontaneous dehiscence 16,19…”
Section: Introductionmentioning
confidence: 99%